(untitled) (Indian Journal of Public Health Research & Development, 2022)
Background: Low back pain (LBP) is an increasingly reported condition, and physical activity (PA) may play an important role. The aim of the present study was to evaluate the proportion of pregnancy-related LBP and its association with type and intensity level of PA during pregnancy. Methods: A longitudinal prospective study was carried out with a cohort of 118 pregnant women. Participants were evaluated in all trimesters. LBP was assessed with a self-reported questionnaire and participants were categorized according to its occurrence. The type and intensity of PA were evaluated using the Pregnancy Physical Activity Questionnaire and categorized into tertiles. Binary logistic regression models were constructed to verify the relationship between LBP and type, the intensity of PA in all trimesters, and LPB pre-pregnancy. Results: LBP was reported by 40.7%, 52.2% and 66.7% of the subjects in the first, second, and third trimesters, respectively. No significant associations were found between LBP and type and intensity of PA. However ,women who had LBP before pregnancy, compared to those who did not, had higher odds of expressing LBP during pregnancy (OR= 3.85, 95% CI: 1.344-11.025). Conclusions: LBP is a common condition and increased during pregnancy. Results of this study suggest that type and intensity of PA are not associated with emerging of LBP during pregnancy.